On a mathematical model for the transmission of the Dengue Disease - Mirasol, Lowilton T.; Escaner, Jose Maria L. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2013)
Dengue, also known as breakbone fever, is the most common and rapidly spreading mosquito-borne disease. The virus, belonging to the genus Flavivirus, is carried and transmitted by the mosquito of the Aedes genus, commonly the Aedes egypti andAedes albopictus. Mosquitoes generally acquire the virus while feeding on the blood of an infected person (WHO, 2009).The study aims to construct a mathematical model, using the SIR framework, that will capture the dynamics of the Dengue disease. Both human population and the vector population will be considered and a control parameter is introduced. We further solve for the basic reproduction rate that will incite the epidemic, investigate the stability of the equilibrium states of the model and derive conditions for stability, if necessary. Numerical simulations will test and validate the model using data obtained from the papers of Pongsumpun et al in [24] and [25] and Rodrigues et al in [8] and [9].
Thesis (M.S. - Applied Mathematics)--University of the Philippines Diliman
Keywords: Dengue; Dengue viruses